2008
DOI: 10.1007/s10549-008-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids and breast cancer chemoprevention

Abstract: Cancer chemoprevention is defined as the use of natural or synthetic agents that reverse, suppress or arrest carcinogenic and/or malignant phenotype progression towards invasive cancer. Phytochemicals obtained from vegetables, fruits, spices, herbs and medicinal plants, such as terpenoids, carotenoids, flavanoids, phenolic compounds, and other groups of compounds have shown promise in suppressing experimental carcinogenesis in various organs. Recent studies have indicated that mechanisms underlying chemopreven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 202 publications
(120 citation statements)
references
References 132 publications
(143 reference statements)
2
107
0
2
Order By: Relevance
“…Triterpenes are a class of phytochemicals with strong anticancer activity toward a variety of cancers, including breast cancer. 20,21) KA is a seco-A-ring oleanene triterpene isolated from S. koetjape. 11,22) In this study, KA exhibited a modest dose dependent antiproliferative activity, with an IC 50 value of 68.88±6.075 μg/ mL.…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenes are a class of phytochemicals with strong anticancer activity toward a variety of cancers, including breast cancer. 20,21) KA is a seco-A-ring oleanene triterpene isolated from S. koetjape. 11,22) In this study, KA exhibited a modest dose dependent antiproliferative activity, with an IC 50 value of 68.88±6.075 μg/ mL.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the number of building blocks, terpenoids are classified into several classes, such as monoterpenes (e.g., carvone, geraniol, d-limonene, and perillyl alcohol), diterpenes (e.g. retinol and trans-retinoic acid), triterpenes [e.g., betulinic acid (BA), lupeol, oleanic acid, and ursolic acid (UA)], and tetraterpenes (e.g., α-carotene, β-carotene, lutein, and lycopene) [45] . The diverse array of terpenoid structures and functions has provoked increased interest in their commercial use.…”
Section: Terpenoidsmentioning
confidence: 99%
“…The diverse array of terpenoid structures and functions has provoked increased interest in their commercial use. Terpenoids have been found to be useful in the prevention and therapy of several diseases, including cancer, and also to have antimicrobial, antifungal, antiparasitic, antiviral, anti-allergenic, antispasmodic, antihyperglycemic, antiinflammatory, and immunomodulatory properties [45][46][47][48] . In addition, terpenoids can be used as protective substances in storing agriculture products as they are known to have insecticidal properties [49] .…”
Section: Terpenoidsmentioning
confidence: 99%
“…Studies have shown that the terpenoids possesses anti-microbial, anti-fungal, anti-parasitic, anti-viral, anti-allergenic, anti-spasmodic, anti-hyperglycemic, anti-inflammatory and immune modulatory properties [173,190,191]. Although early experimental data showed that the most common terpenes (D-limonene) caused increased incidence of renal tubular tumors in male rats, no evidence of any tumor was observed in female rats and mice of both sexes [192].…”
Section: Terpenoidsmentioning
confidence: 99%